Management accounting demystified - Berry, Leonard Eugene (New York : McGraw-Hill, 2006)
This self-teaching guide first explains how and why management accounting is at the intersection of accounting information and decision-making. This book is written to take the mystery out of management; it provides the major accounting concepts and procedure in a concise form. Then, you get details on cost allocation systems, cost analysis, profit planning, operational budgeting, performance evaluations, and more. Featuring end of chapter quizzes and a final exam, this book will teach you the in and out of management accounting in no time at all.
Includes index.
nmn 28/05/13
Loans
Keywords: Managerial accounting; Management accounting; Performance evaluation